'A giant gutter in outer space': Investigating pessimism as rhetorical action in True Detective. Issue 2 (1st November 2017) - Zager, Brian
Perhaps too quickly dismissed as simply 'downbeat' conversational partners, pessimists often face the rhetorical burden of negotiating social contexts dismissive of such an outlook. As the discipline of communication studies aims to investigate different perspectives that are made manifest in the marketplace of ideas, it is noteworthy that heretofore little has been said about the pessimist-as-interlocutor. This article establishes a view of pessimism as rhetorical action by investigating the link between such a philosophical world-view and its embodiment as performative utterance. With this end in mind, it engages with the HBO series True Detective (2014) as an illustrative popular culture media example by which to consider some nuances of this interpersonal phenomenon.